Lipid profile after switching from a TDF (tenofovir disoproxil)-containing to TAF (tenofovir alafenamide)-containing regimen in virologically suppressed people living with HIV - Łomiak, Michał; Gajek, Zofia; Stępnicki, Jan; Lembas, Agnieszka; Mikuła, Tomasz; Wiercińska-Drapało, Alicja (Journal of Medical Science, 2023)
Background. Tenofovir disoproxil fumarate (TDF) or its prodrug, tenofovir alafenamide fumarate (TAF), is currently being recommended in treatment of HIV infection. The distinct pharmacological properties of these two forms of this drug make TAF treatment less nephrotoxic and lead to a better impact on bone density. Nevertheless, a rising concern about TAF's possible metabolic adverse effects exists. This study aimed to evaluate the effects on the lipid profile among ART (antiretroviral therapy) patients switching from a TDF-containing to a TAF-containing regimen in the first year after the switch.Methods. Demographic and clinical data of HIV-positive ART-experienced patients treated in the infectious diseases department was retrospectively collected. Lipid profile change concerning baseline BMI, age, and time of ART duration were analysed.Results. In the group of 36 patients, there was a significant increase in total cholesterol levels (+18.43mg/dl, SD=23.86mg/dl, p
Keywords: antiretroviral therapy; tenofovir disoproxil fumarate; tenofovir alafenamide; lipids; cholesterol; low-density lipoproteins